Assessment of Change of Direction and Agility. Running and Dribbling among Soccer, Basketball and Handball Players: The Concept of “Agility deficit” - Evangelos Bekris; Aristotelis Gioldasis; Emmanouil Zacharakis; Konstantinos Noutsos; Panagiotis Meletakos; Athanasia Smirniotou (Central European Journal of Sport Sciences and Medicine, 2023)
The primary objective of this study is to conduct a comparative analysis of change of direction (COD) and agility among players engaged in soccer, basketball, and handball. Additionally, the researchers introduced the novel concept of “Agility deficit”, aimed at evaluating distinctions between COD and agility during running (COD-R; Agility-R) and dribbling (COD-D; Agility-D). The participant cohort comprises 38 individuals with an average age of 20.63 years, distributed across 13 handball players, 12 soccer players, and 13 basketball players. Statistical analyses, specifically ANOVA accompanied by Tukey’s post hoc comparisons, have been employed to discern significant differences among subgroups. While no noteworthy disparities among groups were observed in both COD-D and Agility-D when participants manipulated the balls using their hands, a marked superiority in performance emerged for soccer players when the balls were manipulated with their legs. Soccer players exhibited expedited responses compared to their basketball and handball counterparts when confronted with a visual stimulus during the Agility-R test (reduced Agility-R deficit). Furthermore, the Agility-D deficit underscored the heightened visual challenge to react in visual stimuli during dribbling in soccer. Independent of the type of ball handling, soccer players consistently demonstrated a diminished Agility-D deficit, affirming their superior visual ability. The performance in Agility-D further revealed that visual ability plays a pivotal role in influencing dribbling ability. The study posits that, for a comprehensive assessment of a player’s visual ability during running or dribbling, interpretations of both Agility-R deficit and Agility-D deficit are imperative. Consequently, the proposed indexes of Agility-R deficit and Agility-D deficit present valuable tools for evaluating players’ COD and Agility abilities during running or dibbling. However, the efficacy of these assessments in real-game situations remains undetermined, requiring further investigation.